2008
DOI: 10.1002/ajp.20573
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in the Kasekela chimpanzees of Gombe National Park, Tanzania

Abstract: Understanding the rates and causes of mortality in wild chimpanzee populations has important implications for a variety of fields, including wildlife conservation and human evolution. Because chimpanzees are long-lived, accurate mortality data requires very long-term studies. Here, we analyze 47 years of data on the Kasekela community in Gombe National Park. Community size fluctuated between 38 and 60, containing 60 individuals in 2006. From records on 220 chimpanzees and 130 deaths, we found that the most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
166
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 43 publications
(62 reference statements)
3
166
2
2
Order By: Relevance
“…The main cause of mortality throughout human evolution until the 20th century must have been infections, as observed in wild chimpanzees and 20th-century hunter-foragers. Longitudinal studies of the Gombe chimpanzees (Tanzania) since 1960 by Goodall and colleagues identified infections in the majority of deaths (67%) for all ages (Table 2) (15). The oldest individuals frequently had prolonged diarrhea (16, p 104).…”
Section: Evolving Demographics Of Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…The main cause of mortality throughout human evolution until the 20th century must have been infections, as observed in wild chimpanzees and 20th-century hunter-foragers. Longitudinal studies of the Gombe chimpanzees (Tanzania) since 1960 by Goodall and colleagues identified infections in the majority of deaths (67%) for all ages (Table 2) (15). The oldest individuals frequently had prolonged diarrhea (16, p 104).…”
Section: Evolving Demographics Of Agingmentioning
confidence: 99%
“…Remarkably, no spontaneous mammary carcinoma has been reported in the great apes. In males 25 years and older, benign prostatic hyperplasia is common, and associated with clinical-grade blood prostate-specific (15,16). This table excludes deaths from poaching and predation; deaths of dependent offspring from maternal death or disability; and from unknown causes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In captivity it is 29 years (66). This doubling of chimpanzee life expectancy is associated with reductions in rates of infection and nutritional stress (38,116). In both chimpanzees and humans, improvements in nutrition and hygiene combined with medical interventions can double life expectancy.…”
Section: Origins Of Heterogeneity In Early Lifementioning
confidence: 99%
“…These assays tell us that wild apes are regularly infected by a variety of virulent pathogens, including simian immunodeficiency virus (SIV) (1), anthrax (2), and malaria (3). The ethical finger has been pointed squarely and quantitatively at researchers and conservationists with the discovery that "spillover" of human respiratory viruses cause about half of deaths among chimpanzees (4,5) and gorillas (6) habituated to human approach for research or tourism. Even more widely recognized have been massive Ebola virus (EBOV) outbreaks in gorillas and chimpanzees (7,8), which have killed roughly one-third of the world gorilla population and led to the 2007 upgrading of western gorillas to Critically Endangered status on the World Conservation Union's Red List of Threatened Species (9).…”
mentioning
confidence: 99%